INTERNATIONALIZATION OF HIGHER EDUCATION IN THE CONTEXT OF RECOVERY OF UKRAINE: GOALS AND CHALLENGES - Mariia Debych (Неперервна професійна освіта: теорія та практика, 2023)
The goal of the study is the analysis of Recovery Plan of Ukraine (draft) on the topic of internationalisation of higher education, its goals and their fulfilment. Goal 4 Internationalization of higher education of Ukraine includes the following steps: introduction of online admission of foreigners to Ukrainian universities on a regular basis; determination of priority measures for learning English; bringing the list of fields of knowledge into compliance with ISCED (stage 1: June 2022 – the end of 2022). To achieve the above goal, several methods have been used, including an internet search, analysis, systematization of evident information. It was found that Ministry of Education and Science of Ukraine provides the regulatory framework for fulfilling goals of the first stage. At the same time it is stated that it is necessary to: approve electronic invitation form; register (registration and issuance by HEIs) electronic invitations using the means of a single interdepartmental electronic platform; interact regarding the approval of electronic invitations; keep records of electronic invitations; introduce the Law of Ukraine «On Employment of the Population» regarding the work of foreigners and stateless persons pursuing higher education in Ukraine; ratify the Global Convention on the Recognition of Qualifications concerning Higher Education (2019). The increase in the volume of state funding of higher education in Ukraine in the conditions of recovery from the consequences of the war with russia compared to the pre-war period is not realistic. The number of Ukrainian and foreign applicants to HEIs will decrease.